The first 60 cases of robotic sacrocolpopexy with the novel HUGO RAS system: feasibility, setting and perioperative outcomes - Panico, Giovanni; Vacca, Lorenzo; Campagna, Giuseppe; Caramazza, Daniela; Mastrovito, Sara; Lombisani, Andrea; Ercoli, Alfredo; Scambia, Giovanni (Frontiers in Surgery, 2023)
Introduction: We present the preliminary report of the first 60 cases of robotic sacrocolpopexy (RSCP) performed with a minimally invasive approach by using the new HUGO RAS system (Medtronic) with the aim of assessing its feasibility, safety and efficacy. Methods: Results in terms of operative time, intraoperative blood loss, postoperative pain, length of hospitalisation, intra and postoperative complications were comparable to previously described laparoscopic and robotic techniques. Results: Urogynecological assessment at three months follow up showed surgical anatomic success in 96,7% of patients (<2 POP-Q stage), while subjective cure rate was 98,3%. Conclusions: This is the first series analysing RSCP outcomes for POP using the new Hugo RAS system. Our results suggest effectiveness both in objective and subjective outcomes, with minimal intra and post operative complications. Larger series as well as longer follow-up are needed to better define advantages and possible disadvantages of this novel system. Our work may represent the basis of future studies to confirm its safety, efficacy and feasibility, and may provide technical notes for other centres that wish to perform RSCP through this innovative system.